Periflexural eruptive lentiginosis after chemotherapy in a girl with Letterer-Siwe disease. - Neri, I.; Infusino, S.D.; Virdi, A.; Patrizi, A. (European Journal of Pediatric Dermatology, 2011)
Langerhans cell histiocytosis (LCH) may be a single-system disease or a multisystem disease with organ dysfunction. Cytotoxic drugs and corticosteroids, alone or in combination, are the treatments for multisystem LCH. We report the case of a young girl who had multiple lentigines localized in periflexural areas, arisen after chemotherapy for Letterer-Siwe disease with skin and bone involvement. The time of lesions onset induces to hypothesize that immune suppression caused by chemotherapy may favor melanocyte proliferation. We hypothesize that the unusual periflexural localization of the lentigines may be due to a greater concentration of melanocytic cells in periflexural areas or a greater concentration of the drugs in the folds due to vasodilation.